Penerapan Metode ASD (Adaptive Software Development) Dalam Pembuatan Sistem Informasi Akuntansi Kas Masuk Dan Kas Keluar Pada CV.Bela Usaha - Nanda Diaz Arizona; Yulia Yulia; Oktavianus Jaka (LPPM Universitas Bina Sarana Informatika, 2022)
Abstract—Information technology is a general term that describes technology that helps us create, convert, store, communicate and provide information. One of the information technologies is information systems, the purpose of using information systems is to form a single entity that integrates data, processes and stores and distributes information. CV Bela Usaha is a business engaged in vehicle washing services such as cars and motorcycles. Until now, CV Bela Usaha has 5 business branches, and every day it is able to provide services for up to 30 transactions at each branch. Cash out transactions need to be carefully recorded and evidence of their use is kept, cash outflows are needed to purchase or pay operating expenses. Where in every transaction, both cash in and cash out are recorded on the media book, they have not used a computer system. Based on the above background, the author will develop an accounting information system to manage cash in and cash out transactions based on a website. By utilizing the cash inflow and outflow management information system at CV Bela Usaha, which is based on this website, the data backup process is easy to do so as to minimize damage and loss of stored data, and make it easier for users to get reports from each transaction.